Low skeletal muscle mass index and all-cause mortality risk in adults: A systematic review and meta-analysis of prospective cohort studies - Wang, Yahai; Luo, Donglin; Liu, Jiahao; Song, Yu; Jiang, Binggang; Jiang, Haichao (PLOS ONE, 2023)
Objective The relationship between low skeletal muscle mass index (SMI) and all-cause mortality risk in the general adults remains unclear. Our study was conducted to examine and quantify the associations between low SMI and all-cause mortality risks. Methods PubMed, Web of Science, and Cochrane Library for primary data sources and references to relevant publications retrieved until 1 April 2023. A random-effect model, subgroup analyses, meta-regression, sensitivity analysis, and publication bias were conducted using STATA 16.0. Results Sixteen prospective studies were included in the meta-analysis of low SMI and the risk of all-cause mortality. A total of 11696 deaths were ascertained among 81358 participants during the 3 to 14.4 years follow-up. The pooled RR of all-cause mortality risk was 1.57 (95% CI, 1.25 to 1.96, P < 0.001) across the lowest to the normal muscle mass category. The results of meta-regression showed that BMI (P = 0.086) might be sources of heterogeneity between studies. Subgroup analysis showed that low SMI was significantly associated with an increased risk of all-cause mortality in studies with a body mass index (BMI) between 18.5 to 25 (1.34, 95% CI, 1.24–1.45, P<0.001), 25 to 30 (1.91, 95% CI, 1.16–3.15, P = 0.011), and over 30 (2.58, 95% CI, 1.20–5.54 P = 0.015). Conclusions Low SMI was significantly associated with the increased risk of all-cause mortality, and the risk of all-cause mortality associated with low SMI was higher in adults with a higher BMI. Low SMI Prevention and treatment might be significant for reducing mortality risk and promoting healthy longevity.